A study on the microwave absorbing honeycomb core embedded with conductive periodic patterned surfaces for the effective dielectric constant. (1st June 2022) - Baek, Sang Min; Lee, Won Jun; Kim, Sang Yong; Kim, Seong Su
Abstract: Periodic patterned surfaces can provide effective dielectric constants to the microwave absorbing honeycomb partition wall depending on the size of the pattern. A characteristic study was conducted for a honeycomb-shaped absorber based on the geometric configurations and material properties. The range of the relative permittivity for increasing the absorption bandwidth of the absorber was determined through a parametric study. The imaginary term of the relative permittivity and depth of the wave propagation direction had a significant impact on the bandwidth of the absorber. Moreover, the materials patterned with carbon black- and graphite-based conductive inks using the screen-printing method were bonded to each other at intervals and stacked to form a honeycomb shape. Several absorber specimens were fabricated, and their absorption capabilities were measured using a free-space measurement system. Based on the results, the utility of a film-based honeycomb absorber that can continuously maintain broadband absorptivity was verified.